Do House Prices Sink or Ride the Wave of Immigration? - Matthew P. Larkin; Zohid Askarov; Chris Doucouliagos; Chris Dubelaar; Maria Klona; Joshua Newton; Tom D. Stanley; Andrea Vocino (Institute of Labor Economics (IZA), 2018)
The sharp rise in international migration is a pressing social and economic issue, as seen in the recent global trend towards nationalism. One major concern is the impact of immigration on housing. We assemble a comprehensive database of 474 estimates of immigration's impact on house prices in 14 destination countries and find that immigration increases house prices, on average. However, attitudes to immigrants moderate this effect. In countries less welcoming to immigrants, house price increases are more limited.
Keywords: F22; R31; 330; immigration; house prices; attitudes; meta-regression